Helicity and winding fluxes as indicators of twisted flux emergence. Issue 1 (2nd January 2021) - MacTaggart, D.; Prior, C.
Abstract : Evidence for the emergence of twisted flux tubes into the solar atmosphere has, so far, come from indirect signatures. In this work, we investigate the topological input of twisted flux tube emergence directly by studying helicity and winding fluxes. In magnetohydrodynamic simulations with domains spanning from the top of the convection zone to the lower corona, we simulate the emergence of twisted flux tubes with a range of different initial field strengths. One important feature of this work is the inclusion of a convectively unstable layer beneath the photosphere. We find approximately self-similar behaviour in the helicity input for the different field strengths considered. As the tubes rise and reach the photosphere, there is a strong input of negative helicity since we consider left-handed twisted tubes. This phase is then followed by a reduction of the negative input and, for low initial field strengths, a net positive helicity input. This phase corresponds to the growing influence of convection on the field and the development of serpentine field structures during emergence. The winding flux can be used to detect when the twisted cores of the tubes reach the photosphere, giving clear information about the input of topologically complex magnetic field into the solar atmosphere. In short, the helicity and winding fluxes can provide much information about how a magnetic field emerges that is not directly available from other sources, such as magnetograms. In evaluating the helicity content of these simulations, we test numerous means for creating synthetic magnetograms, including methods which account for both the evolving geometry and the finite extent of the photosphere. Whilst the general qualitative behaviours are similar in each case, the different forms of averaging do affect the helicity and winding inputs quantitatively.